2013
DOI: 10.1007/s12013-013-9681-x
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Chemo-sensitive Intimal Pulmonary Artery Sarcoma

Abstract: The incidence rate of pulmonary artery sarcoma is very low, but its prognosis is extremely poor. In this case report, after various initial diagnoses at the early stage, pulmonary artery sarcoma was confirmed by surgery. 1 year later, the tumor recurred. After chemotherapy, the patient showed improvement of the subjective complaint of tightness in the chest, and radiological lesion decreased in size. The survival time was extended by 2.5 years. This is the first case report of pulmonary artery sarcoma with suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Patients undergoing multimodal treatments showed a median survival of 24.7 ± 8.5 months [ 7 ]. There is limited information on the role of chemotherapy and radiotherapy in the treatment of this disease [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing multimodal treatments showed a median survival of 24.7 ± 8.5 months [ 7 ]. There is limited information on the role of chemotherapy and radiotherapy in the treatment of this disease [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The literature is largely restricted to case reports and small case series. [6][7][8][9][10][11][12][13][14] Malignant cardiac tumors have a poor prognosis with overall median survival ranging from 6 months to a few years. 5,[15][16][17][18][19][20] The most common symptom at presentation is dyspnea, whereas the complete spectrum includes but is not limited to cardiac symptoms (chest pain, syncope, pericardial effusions, valvular dysfunction, arrhythmias, congestive heart failure, thromboembolic disease, sudden cardiac death) and systemic symptoms of underlying malignant disease (eg, fatigue, fever, weight loss).…”
mentioning
confidence: 99%
“…In patients with PAIS, they have been used either alone or more frequently in combination. Our literature review identified 11 patients who were informative for their tumour response after such a regimen [ 2 , 3 , 5 , 7 , 8 , 9 , 10 ]. There were 3 objective responses (1 complete and 2 partial) and 8 had progressive disease, mirroring the ∼20% objective response rate observed with anthracycline-based regimens in soft tissue sarcomas.…”
Section: Discussionmentioning
confidence: 99%